Polysaccharide‐based porous biopolymers for enhanced bioaccessibility and bioavailability of bioactive food compounds: Challenges, advances, and opportunities. Issue 6 (5th October 2022) - Ubeyitogullari, Ali; Ahmadzadeh, Safoura; Kandhola, Gurshagan; Kim, Jin‐Woo
Abstract: Bioactive food compounds, such as lycopene, curcumin, phytosterols, and resveratrol, have received great attention due to their potential health benefits. However, these bioactive compounds (BCs) have poor chemical stability during processing and low bioavailability after consumption. Several delivery systems have been proposed for enhancing their stability and bioavailability. Among these methods, porous biopolymers have emerged as alternative encapsulation materials, as they have superior properties like high surface area, porosity, and tunable surface chemistry to entrap BCs. This reduces the crystallinity (especially for the lipophilic ones) and particle size, and in turn, increases solubilization and bioavailability. Also, loading BCs into the porous matrix can protect them against environmental stresses such as light, heat, oxygen, and pH. This review introduces polysaccharide‐based porous biopolymers for improving the bioaccessibility/bioavailability of bioactive food compounds and discusses their recent applications in the food industry. First, bioaccessibility and bioavailability are described with a special emphasis on the factors affecting them. Then, porous biopolymer fabrication methods, including supercritical carbon dioxide (SC‐CO2 ) drying, freeze‐drying, and electrospinning and electrospraying, are thoroughly discussed. Finally, common polysaccharide‐based biopolymers (i.e., starch, nanocellulose, alginate, and pectin) used for generating porous materials are reviewed, and their current and potential future food applications are critically discussed.